(untitled) (Communications in Mathematical Research, 2019)
In this paper, a certain class of welded knots K_2n is considered. By calculating the commutators subgroup of fundamental group G_n of welded knot K_2n, n ∈ Z+, we show that these welded knots are not equivalent to each other and they are all not classical knots. Secondly, we study some properties of G_n and obtain that G_n is linear, residually finite and Hopfian.